(untitled) - Braby, Emily (Tuscaloosa, 2003)
This is a responsible and valuable piece of philosophical work. In Aesthetics of the Natural Environment (2003), developed a theory of the 'integrated aesthetic' which integrates subjective and objective approaches to aesthetic experience, judgment and value, and argue that non-instrumental aesthetic valuing of nature potentially grounds an environmental ethic based in respect for nature.
Keywords: Nature (Aesthetics)